Effect of Roof Inclination on Solar Panel’s Energy Output in a South-Western Nigerian City - LAWAL, Muyideen Olalekan; OLAWOLE, Abdulkabir Kayode (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
This work sets up four photovoltaic (PV)-based solar power systems with adjustable solar panel inclination angle stands. It also varies the inclination angle of the solar panel every five days while recording daily energy delivered by the panels. The study finally compares the output energy recorded for different angles. This was done with a view to studying the effect of building roof inclination on the energy deliverable by solar panel installed on it. The set up consists of PV-based solar power systems with adjustable inclination angle stands for four 10 W solar panels which are on the same axis. Each solar panel was connected to a 42 Ah battery through multimeter and charge controller. A 25 W load was used to discharge the battery at night to allow fresh charge from the panels during the day. The multimeter was used to monitor the daily energy delivered. The solar panels were subjected to 0°, 25°, 50° and 75° inclination angles and faced to South direction at the Renewable Energy Laboratory, Osun State University, Osogbo, Nigeria. Data were recorded daily for 20 days by subjecting all panels to the considered angles for five days. The results obtained showed that the average energy delivered by panels installed at the stated inclination angles are 35.35 Wh, 32.25 Wh, 24.1 Wh and 13.95 Wh, respectively. This means that, for a specific building energy need, the steeper the roof (intended for panel installation), the more the amount of solar panel required to meet such energy. The results also showed various expressions that can be used to estimate daily average sun hour (ASH) based on roof inclination. For example, the estimated daily (ASH) for Osogbo and environs can be taken to be 4.22 hour, 3.15 hour and 1.82 hour for 25°, 50° and 75° roof inclinations, respectively.